Concordance between the 2010 and 2015 Resuscitation Guidelines of International Liaison Committee of Resuscitation Councils (ILCOR) members and the ILCOR Consensus of Science and Treatment Recommendations (CoSTRs). (June 2020) - Hingley, Sakura; Booth, Alison; Hodgson, Jasmin; Langworthy, Kristyn; Shimizu, Naoki; Maconochie, Ian
Abstract: Background: Cardiac arrests are associated with poor outcomes. The International Liaison Committee on Resuscitation (ILCOR) evaluates resuscitation science and produced, until 2015, five-yearly consensus on science and treatment recommendations (CoSTRs), informing global resuscitation guidelines. We aimed to identify similarities/differences in resuscitation guidelines from ILCOR members, noting concurrence over time, and CoSTRs influence on these guidelines. Methods: We considered the component elements of paediatric and adult, basic and advanced resuscitation guidelines, published in 2010 and 2015, along with matching ILCOR CoSTRs to examine their influence. We contacted the responsible councils when guidelines were unavailable online. Results: Complete resuscitation guidelines were found for six of the seven ILCOR council members. The Resuscitation Council of Asia only had adult basic life support (BLS) guidelines in English. Three members used the AHA guidelines. Therefore, five rather than seven sets of resuscitation guidelines were compared to the CoSTRs. Concurrence between CoSTRs recommendations and ILCOR council member's resuscitation guidelines has improved over time. Minor variations were identified in both basic and advanced life support, with most variance in paediatric guidelines, but these narrowed over time. Conclusion: The improved concurrence across the resuscitation guidelines with the CoSTRs suggests that ILCOR members accept and hence incorporate CoSTRs recommendations to inform their own resuscitation guidelines. This is one step towards the development of international universal guidelines for adult and paediatric resuscitation.